A Study of Fuel Cell Backup Power in Telecommunication Application - Shiyan Hou; Ran Li (Dianxin kexue)
Based on the fundamentals and advantages of fuel cell backup powers, the innovation and enhance of the fuel cell backup power over general backup power is technically and economically discussed and analyzed. An outdoor telecommunication cabinet solution with fuel cell backup power is illustrated and further research direction on energy saving and emission reduction from fuel cell power in telecom application is suggested.